Perancangan Website Penerimaan Mahasiswa Baru (PMB) dengan Menggunakan Php dan MySql untuk Memudahkan Pendaftar Melalui Online dalam Kepemilikan Kartu Peserta Ujian - Jepri Sirait; Marthin Yohannes Simanjuntak; Elvipson Sinaga (Router : Jurnal Teknik Informatika dan Terapan, 2024)
The manual registration information system for incoming students is still commonly used by certain universities and colleges in Indonesia. However, the challenge lies in the fact that many potential students, especially those living outside urban areas, face difficulties with manual procedures and indeed many colleges still need a more efficient and effective information system to facilitate ownership of exam participant cards. The purpose of this study is to design a new student admissions website using PHP and MySQL to facilitate online registrants in ownership of exam participant cards. The methodology used in this study involves a system development research procedure, specifically focusing on creating a web-based system for new student admissions information that can be accessed via a web browser. The system for new student admissions information was developed using the PHP programming language and utilizing the MySQL database as a database server. The results of the design of this new student admissions website show that the newly implemented web-based student admissions system is able to offer convenience to prospective students in accessing broad information about the admissions process, as well as completing registration procedures, making online payments, and issuing exam participant cards. Hopefully this system will continue to be developed and can be applied in every college.